Evaluation of academic performance at Tishreen University in accordance with the criteria of academic accreditation from the point of view of graduate students (Field study on postgraduate students in college of Literature, Tishreen University) - Akeel, Adeb; Esmail, Lama (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The study is based on a fundamental problem:What are the methods of evaluating academic performance within the standards of academic accreditation at Tishreen University? The study aims to: A statement of the degree of evaluation of postgraduate programs at Tishreen University for Academic Performance. And indicating the degree of availability of academic accreditation standards in the graduate program at Tishreen University. And to reach a set of recommendations, which can help in evaluating academic performance from the point of view of academic accreditation at Tishreen University. Methodology: The descriptive analytical approach. The main findings of the study are as follows: The low academic performance assessment in the Faculty of Arts, Tishreen University from the point of view of graduate students from the perspective of academic accreditation. The factors of learning, teaching, curriculum, supervision, scientific research and faculty are the three most important factors for evaluating academic performance from the perspective of postgraduate students in the college of Literature, Tishreen University. Lack of satisfaction by graduate students for objectives of study programs. Lack of periodic assessment of learning and teaching methods, which led to students' dissatisfaction with learning and teaching methods.